SARS-CoV-2 testing, infections, and hospital admissions with COVID-19 in children and young people in Scotland: a birth cohort study. (November 2021) - Favarato, Graziella; Wijlaars, Linda; Clemens, Tom; Cunningham, Steve; De Stavola, Bianca; Dibben, Chris; Fenton, Lynda; Macfarlane, Alison; McMenamin, Jim; Milojevic, Ai; Taylor, Jonathon; Wood, Rachael; et al.
Abstract: Background: A strong association between deprivation and severe COVID-19 outcomes has been reported among adults. We estimated population-based rates of SARS-CoV-2 testing, laboratory-confirmed infections, and hospital admissions with COVID-19 in children and young people (aged 0–23 years) in Scotland according to sociodemographic risk factors. Methods: We used a birth cohort of all children and young people born in Scotland in 1997–2020, consisting of linked vital registration, maternity, hospital admissions, and SARS-CoV-2 PCR testing data. Participants were followed from birth or Jan 1, 2020 (whichever occurred last) until Dec 31, 2020, death, or emigration. Admissions with COVID-19 were defined as participants with a positive SARS-CoV-2 test during or up to 28 days before admission to hospital, or a relevant International Classification of Diseases version 10 code recorded (U07.1/U07.2). We calculated crude rates of tests, laboratory-confirmed infections, and admissions, by age group, sex, and Scottish Index of Multiple Deprivation (SIMD) quintiles with 95% CIs. Findings: The cohort included 1 230 290 children and young people living in Scotland during 2020. By Dec 31, 2020, 243 958 (19·8%) were tested for SARS-CoV-2 at least once, and 17 709 (7·3%) had tested positive. Infants (aged <2 years) and 18–23-year-olds were most likely to be tested; there was no clear trend in testing rates by SIMD quintile. 18–23-year-olds, females, and those from the most deprived SIMD quintile were most likely to test positive. 379 participants had an admission with COVID-19, corresponding to a rate of 32·0 per 100 000 person-years (95% CI 28·9–35·4). Females (admission rate 35·4 per 100 000 person-years [95% CI 30·9–40·6]) and infants (143·5 per 100 000 person-years [113·3–181·7]) were most likely to be admitted to hospital. There was a clear gradient in hospital admissions by SIMD, with participants in the most deprived quintile (42·9 per 100 000 person-years [36·1–50·8]) experiencing 1·9 times (95% CI 1·3–2·6) the admission rate compared with those in the least deprived (22·6 per 100 000 person-years [16·9–30·3]). Interpretation: Rates of infection and admissions with COVID-19 were associated with area-level deprivation among children and young people. Infants had a relatively low infection rate but the highest admission rate. Analyses examining risk factors, including ethnic group and long-term conditions are underway, to inform the public health response to SARS-CoV-2 in children. Although children and young people in Scotland had low COVID-19-related admission rates versus adults, a socioeconomic gradient was evident, indicating children living in more deprived areas are at increased risk of short-term, and potential long-term, health and education impacts of COVID-19. Funding: UKRI Medical Research Council and the Great Ormond Street Biomedical Research Centre.